A Nexus among Job Autonomy and Employee Vitality, Engagement, Job Satisfaction, and Social Support as a Moderator - Alsakarneh, Asaad; Abu Jaffar, Islam Bassam; Al-Shakri, Kadri S. (International Review of Management and Marketing, 2026)
It is becoming increasingly complex for modern organizations, especially those in high-pressure banking, to balance employee work, life, and well-being. Pressures at work can stop innovation and hinder long-term success, so we should examine what helps employees succeed at work. This study examines how job autonomy impacts employee vitality, engagement, and job satisfaction in Jordanian commercial banks while considering social support as a moderator. This research uniquely examines the non-Western service sector, which has received little attention. The data of 320 bank employees were analysed using Smart pls software structural equation modeling. The results back every hypothesis, demonstrating that greater job autonomy in one’s job helps increase vitality, engagement, and satisfaction and that social support reinforces these positive results. This research adds new ideas to the Self-Determination Theory and the Job Demands-Resources model that are meaningful in Jordan’s work culture. This study adds to the theory by supporting these frameworks in a different context and provides valuable recommendations for HR in banking. Using these findings, organizations can make workplace changes supporting leader autonomy and firm direction, improving work satisfaction and effective performance. This research reveals that Western theories on autonomy are relevant everywhere, but how they are implemented has changed in specific Middle Eastern contexts.